TRAINING ON WRITING PROPOSALS HIBAH DIKTI ABOUT COMMUNITY SERVICE FOR USCND LECTURERS - Julianda, Ema; Diah Setiawati; Ridwan, Ridwan; Rina Purnama Sari; Dedi Irawan (CV. Naskah Aceh, 2025)
The difficulty of lecturers in scientific publications is the low level of dedication and research conducted by lecturers. One of the causes of low research among lecturers, especially in the USCND environment, is the lack of national competitive PkM proposals that pass the selection. The purpose of this activity is to improve lecturers' knowledge and skills in compiling national competitive proposals. This community service activity will be carried out in several stages, namely 1) Coordination with all related parties, including the USCND Chancellor; 2) Training on compiling national competitive proposals; 3) Assistance in writing proposals; 4) Focus group discussions on several problems that occur, solutions and follow-up plans. At this stage, a comprehensive evaluation of the activity is also carried out. After participating in this activity, participants are expected to be able to make considerations for the national competitive PkM scheme, utilizing knowledge and information to support plans and facilitate the preparation of proposals.